The Use of Remotely Sensed Information within a Flood Risk Management and Analysis Tool (GARI) - Chokmani, Karem; Oubennaceur, Khalid; Tanguy, Marion; Poulin, Jimmy; Gauthier, Yves; Latapie, Romain; Bernier, Monique (IGARSS 2019 - 2019 IEEE International Geoscience and Remote Sensing Symposium, 2019)
Floods are the most common natural hazard worldwide. GARI is a flood risk management and analysis tool that is being developed by the Environmental and Nordic Remote Sensing Group (TENOR) of INRS in Quebec City (Canada). Beyond mapping the flooded areas and water levels, GARI allows for the estimation, analysis and visualization of flood risks for individuals, residential buildings, and population. Information can therefore be used during the different phases of flood risk management. In the operational phase, GARI can use satellite radar images to map in near real-time the flooded areas and water levels. It uses an innovative approach that combines Radarsat-2 and hydraulic data, specifically flood return period data. Information from the GARI enable municipalities and individuals to anticipate the impacts of a flood in a given area, to mitigate these impacts, to prepare, and to better coordinate their actions during a flood.
ISSN: 2153-7003

Influence of instrumentation on long temperature time series - Acquaotta, Fiorella; Fratianni, Simona; Aguilar, Enric; Fortin, Guillaume (Climatic Change, 2019)
In time series of essential climatological variables, many discontinuities are created not by climate factors but changes in the measuring system, including relocations, changes in instrumentation, exposure or even observation practices. Some of these changes occur due to reorganization, cost-efficiency or innovation. In the last few decades, station movements have often been accompanied by the introduction of an automatic weather station (AWS). Our study identifies the biases in daily maximum and minimum temperatures using parallel records of manual and automated observations. They are selected to minimize the differences in surrounding environment, exposition, distance and difference in elevation. Therefore, the type of instrumentation is the most important biasing factor between both measurements. The pairs of weather stations are located in Piedmont, a region of Italy, and in Gaspe Peninsula, a region of Canada. They have 6years of overlapping period on average, and 5110 daily values. The approach implemented for the comparison is divided in four main parts: a statistical characterization of the daily temperature series; a comparison between the daily series; a comparison between the types of events, heat wave, cold wave and normal events; and a verification of the homogeneity of the difference series. Our results show a higher frequency of warm (+10%) and extremely warm (+35%) days in the automated system, compared with the parallel manual record. Consequently, the use of a composite record could significantly bias the calculation of extreme events.
MAG ID: 2971678736

Spatialisation des processus d’embâcles dans le bassin versant de la rivière l’Acadie, Montérégie : une approche hydrogéomorphologique - Plante Lévesque, Valérie; Boucher, Étienne; Proulx, Guillaume (Revue des sciences de l’eau, 2019)
La rivière L’Acadie, située en Montérégie (Québec, Canada), est un affluent de la rivière Richelieu et s’écoule vers le nord. Des inondations hivernales ayant de lourds impacts sur les milieux habités des municipalités de Chambly et de Carignan sont fréquentes sur cette rivière. Alors qu’au Québec on privilégie une approche hydrologique basée sur la récurrence des inondations en eau libre pour aménager les rives et la plaine inondable, l’approche hydrogéomorphologique permet de spatialiser les processus fluviaux qui posent un risque pour les communautés à partir d’une étude détaillée et systématique des formes du paysage fluvial. Cette approche permet d’acquérir une meilleure idée de l’impact de certains processus fluviaux tels que les embâcles de glace sur l’environnement humain et naturel. La présente recherche a pour objectif de spatialiser les propriétés et les impacts géomorphologiques du régime d’embâcles de glace au sein du bassin versant de la rivière L’Acadie. Des caractérisations des propriétés du bassin versant, du chenal, puis des berges de la rivière sont effectuées afin de localiser les problèmes d’embâcles de glace et décrire l’intensité de leur empreinte morphologique sur le milieu. De ces résultats découle une typologie des berges à laquelle est jumelée une analyse de la fréquence des évènements par l’étude des cicatrices glacielles sur la végétation riveraine. L’analyse démontre comment la morphométrie du chenal, la présence d’agriculture ainsi que l’héritage de la dernière glaciation quaternaire affectent le dynamisme du régime d’embâcles de glace qui se concentre en aval de la rivière. , L’Acadie River is a tributary of the Richelieu River that flows northwards through the southwestern region of Montérégie (Quebec, Canada). The river is well known for its frequent winter floods that severely affect the nearby towns of Chambly and Carignan. Even though legislation in Quebec has an approach based on the frequency of open water floods to control riverbanks and floodplain development, the study of river forms, known as hydrogeomorphology, provides a more comprehensive understanding of the impact of fluvial processes such as river ice jams. The main objective of this research is to gain knowledge on river ice dynamics based on their spatialization within L’Acadie River watershed. The characterization of the watershed, channel, and river bank properties and features is based on a hydrogeomorphological approach to spatialize river ice activity along the river. The study emphasizes that watershed properties, the ubiquity of agriculture, and the legacy of the Quaternary ice period in the area are all factors that contribute to ice scouring activity in the downstream section of the main channel.
Keywords: Ouvrage_Collectif_Numéro1

Flooding Related Consequences of Climate Change on Canadian Cities and Flow Regulation Infrastructure - Gaur, Ayushi; Gaur, Abhishek; Yamazaki, Dai; Simonovic, Slobodan P. (Water, 2019)
This study discusses the flooding related consequences of climate change on most populous Canadian cities and flow regulation infrastructure (FRI). The discussion is based on the aggregated results of historical and projected future flooding frequencies and flood timing as generated by Canada-wide hydrodynamic modelling in a previous study. Impact assessment on 100 most populous Canadian cities indicate that future flooding frequencies in some of the most populous cities such as Toronto and Montreal can be expected to increase from 100 (250) years to 15 (22) years by the end of the 21st century making these cities highest at risk to projected changes in flooding frequencies as a consequence of climate change. Overall 40–60% of the analyzed cities are found to be associated with future increases in flooding frequencies and associated increases in flood hazard and flood risk. The flooding related impacts of climate change on 1072 FRIs located across Canada are assessed both in terms of projected changes in future flooding frequencies and changes in flood timings. Results suggest that 40–50% of the FRIs especially those located in southern Ontario, western coastal regions, and northern regions of Canada can be expected to experience future increases in flooding frequencies. FRIs located in many of these regions are also projected to experience future changes in flood timing underlining that operating rules for those FRIs may need to be reassessed to make them resilient to changing climate.
MAG ID: 2908236810

Risk assessment strategies for early detection and prediction of infectious disease outbreaks associated with climate change - Rees, Ee; Ng, V; Gachon, P; Mawudeku, A; McKenney, D; Pedlar, J; Yemshanov, D; Parmely, J; Knox, J (Canada Communicable Disease Report, 2019)
Keywords: Gachon_Philippe

Stratégie d’évaluation des risques servant à la détection précoce et à la prédiction des éclosions de maladies infectieuses associées aux changements climatiques - Rees, Ee; Ng, V; Gachon, P; Mawudeku, A; McKenney, D; Pedlar, J; Yemshanov, D; Parmely, J; Knox, J (Relevé des maladies transmissibles au Canada, 2019)
Keywords: Gachon_Philippe

Supporting and Accompanying Young People After the Lac-Mégantic Train Derailment (Quebec, Canada) - Généreux, Mélissa; Maillet, Marie-Claude; Nault-Horvath, Elise; Stewart, Cindy (Prehospital and Disaster Medicine, 2019)
Introduction:In July 2013, a train transporting oil derailed and exploded in Lac-Mégantic, causing major human, environmental, and economic impacts. A community-based survey of people aged 10-25, conducted in 2017, revealed that many young people suffer in silence and report feeling isolated. These observations led to the conclusion that we must make room for young people, and that opportunities for engagement and participation must be provided within the community.Aim:The Public Health Direction of Estrie aimed to identify strategies to promote health and wellbeing for young people living in and around Lac-Mégantic.Methods:A collective reflection half-day was hosted with sixty key stakeholders (school board, other education institutions, health and social services, community sector, municipal/political sector, parents, youth). Throughout the event, participants were invited to build on and learn from accomplishments and experiential knowledge, and develop a common vision of the solutions to be pursued or implemented. All qualitative data sources (verbal and written data from large- and sub-group activities) were analyzed through a content analysis.Results:Several themes (i.e. potential solutions) emerged from the analysis: common venue, diversified activities, communication, collaboration, involvement, support for at-risk youth, intergenerational component, etc. Participants agreed on four priorities for action: 1) creating a gathering place, 2) establishing a Youth Committee, 3) supporting adults working with youth, and 4) fostering a better flow of information.Discussion:Several positive outcomes of the collective reflection half-day were observed, including the mobilization of the participants who greatly appreciated the event, and many promising ideas launched by stakeholders. A social worker is now fully dedicated to supporting youth wellbeing and engagement in Lac-Mégantic. A Youth Committee has been established and projects by and for youth are being implemented. Bottom-up approaches to identify solutions to complex situations are not only effective but also respectful of the local culture.
Keywords: Généreux_Mélissa

Climate Change Impacts on Catchment Hydrology in Eastern Canada - Aygün, O.; Kinnard, C.; Campeau, S. (2019)
Snowmelt dominated regions are receiving increasing attention due to their noticeably rapid response to ongoing climate change, which raises concerns about the altered hydrological risks under climate change scenarios. This study aims to assess the climate change impacts on hydrology over two contrasted catchments in southern Québec: Acadie River and Montmorency River catchments. These river catchments represent two predominant landscapes of the St. Lawrence River watershed; an intensive farming landscape in the south shore lowlands and the forested landscape on the Canadian Shield on the north shore, respectively. In this study, a physically based hydrological model has been developed using the Cold Regions Hydrological Model (CRHM) for both of the catchments. The hydrological model outputs showed that we were able to simulate snow surveys and discharge measurements with a reasonable accuracy for both catchments. The acceptable performance of the model along with the strong physical basis of structure suggested that this model could be used for climate change sensitivity simulations. Based on the climate scenarios reviewed, a temperature increase up to 8°C and an increase in total precipitation up to 20% were analysed for both of the catchments. Both catchments were found to be sensitive to climate change, however the degree of sensitivity was found to be catchment specific. Snow processes in the Acadie River catchment were simulated to be more sensitive to warming than in the Montmorency River catchment. In case of 2°C warming, reduction in peak SWE was not be able to be compensated even by increased precipitation scenario. Given that, the Acadie River has already a mixed flow regime, even if 2°C warming is combined with an increase in precipitation, pluvial regime kept becoming more dominant, resulting in higher peaks of rain events. On the other hand, even 3°C of warming did not modify the flow regime of the Montmorency River. While there is shift towards earlier peak spring flows in both catchments, the shift was found to be more pronounced in the Acadie River. An earlier occurrence of snowmelt floods and an overall increase in winter streamflow during winter have been simulated for both catchments, which calls for renewed assessments of existing water supply and flood risk management strategies.
Conference Name: AGU Fall Meeting Abstracts ADS Bibcode: 2019AGUFM.C33B1572A
Keywords: Kinnard_Christophe

Communicating disaster risk? An evaluation of the availability and quality of flood maps - Henstra, Daniel; Minano, Andrea; Thistlethwaite, Jason (Natural Hazards and Earth System Sciences, 2019)
Abstract. One of the key priorities for disaster risk reduction is to ensure decision makers, stakeholders, and the public understand their exposure to disaster risk, so that they can take protective action. Flood maps are a potentially valuable tool for facilitating this understanding of flood risk, but previous research has found that they vary considerably in availability and quality. Using an evaluation framework comprising nine criteria grounded in existing scholarship, this study assessed the quality of flood maps available to the public in Canadian communities located in designated flood risk areas. It found that flood maps in most municipalities (62 %) are low quality (meeting less than 50 % of the criteria) and the highest score was 78 % (seven of nine criteria met). The findings suggest that a more concerted effort to produce high-quality, publicly accessible flood maps is required to support Canada's international commitment to disaster risk reduction. Further questions surround possible weighting of quality assessment criteria, whether and how individuals seek out flood maps, and how flood risk information could be better communicated using modern technology.
Keywords: Ouvrage_Collectif_Numéro1

Psychosocial Stress, Sedentary Behavior, and Physical Activity during Pregnancy among Canadian Women: Relationships in a Diverse Cohort and a Nationwide Sample - Sinclair, Isabelle; St-Pierre, Myriane; Elgbeili, Guillaume; Bernard, Paquito; Vaillancourt, Cathy; Gagnon, Sonia; Dancause, Kelsey Needham (International Journal of Environmental Research and Public Health, 2019)
Background: Past research shows that psychosocial stress and distress predict sedentary behavior and physical activity, but few studies focus on pregnant women. Our objective was to analyze relationships between psychosocial stress and distress with sedentary behavior and physical activity among pregnant women in Canada. Methods: We analyzed objectively-measured sedentary behavior and physical activity at 16–18, 24–26, and 32–24 weeks pregnancy in a sociodemographically diverse cohort of 70 women in Montreal, Canada. Participants completed the Perceived Stress Questionnaire and wore an accelerometer for 3 days that quantified sitting time and steps per day. We used univariate general linear models to analyze relationships between perceived stress with sedentary behavior and physical activity at each evaluation. To assess generalizability, we analyzed relationships between psychological distress with self-reported leisure-time sedentary behavior and daily energy expenditure in transportation and leisure physical activities among a sample representative of 166,095 women in the Canadian Community Health Survey. Results: In the Montreal cohort, we observed a positive association between perceived stress and sitting time, with small to moderate effect sizes (partial η2 = 0.08–0.16). We observed negative relationships between perceived stress and steps per day at the first two evaluations only, with small to moderate effect sizes (partial η2 = 0.08–0.11). Relationships for sedentary behavior were similar in the nationwide sample, but with smaller effect sizes (partial η2 = 0.02). There were no relationships between distress and physical activity in the nationwide sample. Conclusion: Psychosocial stress represents one risk factor for sedentarity, with relationships evident throughout pregnancy and at the population level. Relationships with physical activity are less consistent, but stress might represent a risk factor for low physical activity in early to mid-pregnancy. Results might guide the development of more comprehensive interventions targeting stress, sedentarity, and physical activity. In particular, integrating psychosocial health into interventions to reduce sedentarity, and including concrete guidelines on sedentary behavior in psychosocial health interventions, might be prioritized.

Les impacts des changements climatiques sur la santé au Québec : l’exemple de l’Estrie - Petit, Geneviève; Lachance, Éric; Généreux, Mélissa; Barbeau-Meunier, Charles-Antoine; Pinsonneault, Linda; Dao, Huy Hao; Milot, Marie-Christine; Baron, Geneviève; Carignan, Alex (Le Climatoscope, 2019)
L’Organisation mondiale de la Santé (OMS) soutient que les changements climatiques représentent la plus grande menace pour la santé dans le monde au 21e siècle. Ceux-ci influencent négativement plusieurs déterminants sociaux et environnementaux de la santé comme l’accessibilité à la nourriture et la qualité de cette dernière, l’eau et l’air. Blessures, impacts psychosociaux, aggravation de maladies respiratoires, malnutrition, maladies infectieuses, décès : les conséquences sanitaires sont susceptibles d’affecter les populations sur tous les continents. Le Canada se réchauffe deux fois plus rapidement que la moyenne mondiale en raison de sa proximité au pôle Arctique, où le réchauffement est accéléré comparativement à l’équateur (Bush et Lemmen, 2019). Ainsi, le Québec n’est certainement pas à l’abri des changements climatiques. Dans le Sud de la province, les températures moyennes observées ont augmenté de plus d’un degré depuis 1970 et des répercussions se font déjà sentir dans notre environnement. Ce réchauffement, accompagné d’une plus grande variabilité du climat (augmentation du risque d’orages, de tempêtes et d’extrêmes hydrométéorologiques en général), représente un défi grandissant pour les professionnel.le.s de la santé. Dans la région de l’Estrie, les professionnel.le.s de santé publique ont effectué une analyse qui leur ont permis d’identifier quatre principaux problèmes environnementaux associés aux changements climatiques, soit : les vagues de chaleur; les inondations; les tiques à pattes noires; le pollen de l’herbe à poux. Ces problèmes ont des impacts importants sur la santé, c’est-à-dire potentiellement graves ou qui touchent un grand nombre de personnes. Le stress et les pertes (humaines et matérielles) engendrées par ces différents problèmes environnementaux peuvent aussi représenter une source majeure de problèmes psychologiques significatifs pouvant persister dans le temps. De plus, ces impacts sont variables selon les différents contextes sociaux des individus et des communautés, générant des inégalités sociales de santé.
Keywords: Généreux_Mélissa

Seniors Who Experienced the Lac-Mégantic Train Derailment Tragedy: What Are the Consequences on Physical and Mental Health? - Maltais, Danielle; Tremblay, Anne-Julie; Labra, Oscar; Fortin, Geneviève; Généreux, Mélissa; Roy, Mathieu; Lansard, Anne-Lise (Gerontology and Geriatric Medicine, 2019)
Introduction: In July 2013, a train derailment caused the death of 47 people and destroyed the downtown area in the city of Lac-Mégantic (Quebec, Canada). This tragedy had several impacts on this small community. Method: Three years after this disaster, we used a representative population-based survey conducted among 800 adults (including 265 seniors aged 65 or above) to assess the physical and mental health of seniors. Results: Several differences were observed in seniors’ physical and mental health based on their level of exposure to the tragedy. Nearly half of seniors highly exposed to the train derailment (41.7%) believe that their health has deteriorated in the past 3 years. The majority of seniors highly exposed to the train derailment (68.7%) also show symptoms of posttraumatic stress disorders. Seniors highly or moderately exposed to the tragedy were also more likely to have found positive changes in their personal and social life as compared with nonexposed seniors. Discussion: A technological disaster such as a train derailment still had negative impacts on seniors’ physical and mental health 3 years later. Conclusion: Public health authorities must tailor prevention and promotion programs to restore health and well-being in this population.
Keywords: Généreux_Mélissa

Monitoring Adverse Psychosocial Outcomes One and Two Years After the Lac-Mégantic Train Derailment Tragedy (Eastern Townships, Quebec, Canada) - Généreux, Mélissa; Maltais, Danielle; Petit, Geneviève; Roy, Mathieu (Prehospital and Disaster Medicine, 2019)
Introduction:In July 2013, a train carrying 72 cars of crude oil derailed in the town of Lac-Mégantic (Eastern Townships, Quebec, Canada). This disaster provoked a major conflagration, explosions, 47 deaths, the destruction of 44 buildings, the evacuation of one-third of the local population, and an unparalleled oil spill. Notwithstanding the environmental impact, many citizens of this town and in surrounding areas have suffered and continue to suffer substantial losses as a direct consequence of this catastrophe.Problem:To tailor public health interventions and to meet the psychosocial needs of the community, the Public Health Department of Eastern Townships has undertaken repeated surveys to monitor health and well-being over time. This study focuses on negative psychosocial outcomes one and two years after the tragedy.Methods:Two cross-sectional surveys (2014 and 2015) were conducted among large random samples of adults in Lac-Mégantic and surrounding areas (2014: n = 811; 2015: n = 800), and elsewhere in the region (2014: n = 7,926; 2015: n = 800). A wide range of psychosocial outcomes was assessed (ie, daily stress, main source of stress, sense of insecurity, psychological distress, excessive drinking, anxiety or mood disorders, psychosocial services use, anxiolytic drug use, gambling habits, and posttraumatic stress symptoms [PSS]). Exposure to the tragedy was assessed using residential location (ie, six-digit postal code) and intensity of exposure (ie, intense, moderate, or low exposure; from nine items capturing human, material, or subjective losses). Relationships between such exposures and adverse psychosocial outcomes were examined using chi-squares and t-tests. Distribution of outcomes was also examined over time.Results:One year after the disaster, an important proportion of participants reported human, material, and subjective losses (64%, 23%, and 54%, respectively), whereas 17% of people experienced intense exposure. Participants from Lac-Mégantic, particularly those intensely exposed, were much more likely to report psychological distress, depressive episode, anxiety disorders, and anxiolytic drug use, relative to less-exposed ones. In 2015, 67% of the Lac-Mégantic participants (76% of intensely exposed) reported moderate to severe PSS. Surprisingly, the use of psychosocial services in Lac-Mégantic declined by 41% from 2014 to 2015.Conclusion:The psychosocial burden in the aftermath of the Lac-Mégantic tragedy is substantial and persistent. Public health organizations responding to large-scaling disasters should monitor long-term psychosocial consequences and advocate for community-based psychosocial support in order to help citizens in their recovery process.
Keywords: Généreux_Mélissa

From Science to Policy and Practice: A Critical Assessment of Knowledge Management before, during, and after Environmental Public Health Disasters - Généreux, Mélissa; Lafontaine, Marc; Eykelbosh, Angela (International Journal of Environmental Research and Public Health, 2019)
Canada regularly faces environmental public health (EPH) disasters. Given the importance of evidence-based, risk-informed decision-making, we aimed to critically assess the integration of EPH expertise and research into each phase of disaster management. In-depth interviews were conducted with 23 leaders in disaster management from Canada, the United States, the United Kingdom, and Australia, and were complemented by other qualitative methods. Three topics were examined: governance, knowledge creation/translation, and related barriers/needs. Data were analyzed through a four-step content analysis. Six critical success factors emerged from the analysis: blending the best of traditional and modern approaches; fostering community engagement; cultivating relationships; investing in preparedness and recovery; putting knowledge into practice; and ensuring sufficient human and financial resources. Several promising knowledge-to-action strategies were also identified, including mentorship programs, communities of practice, advisory groups, systematized learning, and comprehensive repositories of tools and resources. There is no single roadmap to incorporate EPH expertise and research into disaster management. Our findings suggest that preparation for and management of EPH disaster risks requires effective long-term collaboration between science, policy, and EPH practitioners at all levels in order to facilitate coordinated and timely deployment of multi-sectoral/jurisdictional resources when and where they are most needed.
Keywords: Généreux_Mélissa

Gouvernance collaborative d'appréciation des risques des systèmes essentiels en contexte de changements climatiques : cas de deux MRC au Québec - Lépine, Caroline; Baril, Geneviève; Hémond, Yannick; Therrien, M.-C.; Robert, Benoît (2019)
Keywords: Hémond_Yannick

Risques d’inondation et vulnérabilité : l’exemple du bassin versant de la rivière Kennebecasis, Nouveau-Brunswick, Canada. - Fortin, Guillaume; Poirier, Charlotte; Duhamel, Françis; Germain, Daniel (2019)
La province du Nouveau-Brunswick, situee dans l’est du Canada, est tres affectee par les inondations. Bien que moins documentee que l’alea, la dimension humaine du risque que represente la vulnerabilite est importante pour l’adaptation des populations. Cet article fait un survol des principaux concepts lies a la vulnerabilite et presente leur application a l’echelle d’un bassin versant de taille moyenne. Les resultats montrent la necessite de considerer simultanement la perception et la preparation au risque d’inondation. En effet, si certains residents dans les zones a risque ont une bonne connaissance des inondations et une perception realiste du risque, cela ne se traduit pas necessairement par une preparation adaptee et adequate face au risque. La reduction du risque passe indeniablement par une meilleure sensibilisation et education de la population.
MAG ID: 3012134137